Corporate Governance: Theoretical Analysis and Examination of a Sample of 22 Companies in French Guyana - Chim, Paul Roselé (American Journal of Management, 2021)
Governance plays an essential role in the functioning and performance improvement of companies, which define their governance structure in order to adapt to changes in the environment. Imposing identical governance rules on all companies can disrupt or even destabilize a governance system that is otherwise globally coherent and efficient. Choosing a system of governance means that the mechanisms of the company control the actions of the managers and analyze them as fulfilling their obligations to the principals, the shareholders. Thus, two groups stand out, namely the managers and the shareholders. So, how to satisfy all parties correctly? What management objectives should be attributed to managers? What guarantee can we have on the sincerity of the executive power on the social interest? This paper proposes to answer these three questions by examining governance through the study of a sample of 22 firms in French Guyana. It examines the literature on corporate governance, and the link between theories and contractualization, to conduct the quantitative investigation, and interpretation of the results.